(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
This article examines the impact of economic sanctions against the Russian Federation on global trade, macroeconomic dynamics and declining prosperity using a model consisting of three groups of countries: Russia and the allied states, the countries imposing sanctions (EU, UK, USA, etc.), and third countries (Turkey, India, China in the study, the economic sectors affected by sanctions are conditionally divided into related and unrelated to the oil and gas industry. An analysis of the impact of sanctions on the foreign economic situation using the classifications adopted above allows us to determine their key effects on the Russian economy and the economies of the countries that authored the sanctions, and allows us to draw conclusions about the effectiveness of the methods of economic interaction between the collective West and Russia.